Global research status and frontiers on ferroptosis in hepatocellular carcinoma: a comprehensive bibliometric and visualized analysis - Zhu, Jiayu; Luo, Shengping; Yu, Fei; Sun, Kewei (Frontiers in Immunology, 2025)
ObjectiveThe purpose of this study was to analyze the research hotspots and future trends in the field of ferroptosis in hepatocellular carcinoma in the past 10 years by using bibliometrics and visualization software, and to provide reference for future research directions in this field.MethodsThe Web of Science database was searched from January 1, 2012, to October 30, 2024, and the annual publication volume, countries, institutions, journals, authors, references, keywords, and other information in this field were analyzed by bibliometrics, VOSviewer, and CiteSpace.ResultsA total of 645 English articles from 729 institutions in 32 countries were included in this study, with 4545 authors published in 261 journals. In the past three years, 518 articles were published, accounting for 80.3%. China has the most publications, followed by the United States. Frontiers in Oncology had the highest number of papers (n=26), while Cell had the highest number of citations (n=1206). The current research mainly focuses on two aspects: one is the study of the mechanism of ferroptosis to explore new therapeutic targets, and the other is the exploration of therapeutic methods, such as photodynamic therapy and nanomaterials, in order to inhibit the proliferation of tumor cells, reduce drug resistance, and enhance the efficacy by regulating ferroptosis, which may become a future development trend.ConclusionIn recent years, there have been increasing studies on the association between ferroptosis and hepatocellular carcinoma. This is the first comprehensive bibliometric study, which provides a reliable reference for future research in this field and promotes its further development.